Determinación de la concentración de sólidos suspendidos totales (SST) y metales pesados en la cuenca del Río Morote, Nicoya, Guanacaste. - Sánchez Murillo, Ricardo (2009)
The Total Suspended Solids (TTS) and heavy metal concentrations of Morote River Basin were determined. The project includedsix sampling campaigns between April 2003 and May 2005. The sampling points in the Morote River were selected from the high basin to the mouth of the river in the Gulf of Nicoya. During the rainy season the concentrations of TTS exceed the value of 200 mg/L in the mouth of the river. An enrichment of the sediments was found from the river-bed with heavy metals such as copper, cadmium, nickel and iron but enrichment with lead was not found. In the dry season the concentration of zinc was colose to the allotted maximum value (200 mg/kg) which has been established for the Envoronmental Protection Agency of the United States (EPA).